We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
101
1
avatar

Let \(F_1=(10,2)\)and \(F_2 = (-16,2)\) . Then the set of points \(P \) such that \(|PF_1 - PF_2| = 24\) form a hyperbola. The equation of this hyperbola can be written as \(\frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1\). Find \(h + k + a + b.\)

 Aug 4, 2019
 #1
avatar+23295 
+2

Let \(F_1=(10,2)\) and  \(F_2 = (-16,2)\). Then the set of points \(P\) such that \(|PF_1 - PF_2| = 24\) form a hyperbola.
The equation of this hyperbola can be written as \(\dfrac{(x - h)^2}{a^2} - \dfrac{(y - k)^2}{b^2} = 1\).
Find \(h + k + a + b\).

 

\(\begin{array}{|rcll|} \hline \mathbf{|PF_1 - PF_2|} &=& \mathbf{2a} \\ |PF_1 - PF_2| &=& 24 \\ 2a&=& 24 \\ \mathbf{a} &=& \mathbf{12} \\ \hline \end{array}\)

 

\(\begin{array}{|lrc|} \hline \mathbf{\text{Focus}_1:}& \mathbf{F_1(h+ae,k)} \\ & F_1(10,2): & h+ae = 10 \quad (1) \\ && \mathbf{ k =2} \\ \hline \mathbf{\text{Focus}_2:}& \mathbf{F_2(h-ae,k)} \\ & F_2(-16,2): & h-ae = -16\quad (2) \\ && \mathbf{ k =2} \\ \hline \end{array} \)

 

\(\begin{array}{|lrcll|} \hline (1)+(2): & h+ae + h-ae &=& 10-16 \\ & 2h &=& -6 \\ & \mathbf{ h }&=& \mathbf{-3} \\ \hline \end{array} \)

 

\(\begin{array}{|lrcll|} \hline (1) & h+ae &=& 10 \quad |\quad h=-3 \\ & -3+ae &=& 10 \\ & \mathbf{ ae }&=& \mathbf{13} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline a^2 + b^2 &=& (ae)^2 \\ 12^2+b^2 &=& 13^2 \\ b^2 &=& 13^2-12^2 \\ b^2 &=& 169-144 \\ b^2 &=& 25 \\ \mathbf{ b }&=& \mathbf{5} \\ \hline \end{array}\)

 

\(\begin{array}{rcll} && \mathbf{h + k + a + b} \\ &=& -3 + 2 +12+5 \\ &=& \mathbf{16} \\ \end{array}\)

 

laugh

 Aug 5, 2019

13 Online Users